FROM CHALLENGES TO OPPORTUNITIES: WOMEN ENTREPRENEURS IN BANGLADESH AND THEIR PATH FORWARD - Sarkar, Popy Rani (International Journal of Small and Medium Enterprises, 2024)
In a developing nation like Bangladesh, entrepreneurship plays a vital role in driving economic development. However, women face numerous challenges that hinder their success as entrepreneurs. Given that women make up half of the population, it is essential to promote their participation in entrepreneurial activities by addressing the obstacles they encounter and identifying available opportunities. This study examines the current landscape of women’s entrepreneurship in Bangladesh, focusing on the barriers faced by female entrepreneurs and the prospects for growth, along with strategies to turn these challenges into viable opportunities. To fulfill its objectives, the research employs survey data collected from 60 women entrepreneurs in Bangladesh through a structured questionnaire. Various statistical methods, including descriptive statistics, correlation analysis, ANOVA, and regression coefficients, are employed to present the findings in a clear and interpretable manner. The results reveal a positive correlation between women’s engagement in entrepreneurship and their potential for success, which contributes to their entrepreneurial endeavors. Conversely, the study identifies a weaker positive relationship between women’s entrepreneurial activities and the challenges they face in self-employment. Despite these obstacles, it is evident that women can enhance their entrepreneurial pursuits by effectively addressing the barriers in their way. The findings of this study advocate for government initiatives that promote women’s participation in entrepreneurship and provide the necessary support to overcome these challenges. Such initiatives are crucial for fostering sustainable economic growth in Bangladesh. By increasing women’s engagement in entrepreneurship, the nation can significantly advance its economic development goals. JEL Classification Codes: J16, J16, O10, O53.